2017
DOI: 10.1039/c7dt00909g
|View full text |Cite
|
Sign up to set email alerts
|

Formation of mono- and binuclear neodymium(iii)–gluconate complexes in aqueous solutions in the pH range of 2–8

Abstract: The complex formation between Nd(iii) and d-gluconate (Gluc) is of relevance in modelling the chemical equilibria of radioactive waste repositories. In the present work, the formation of NdGlucH complexes at 25 °C and pH = 2-8 was studied via spectrophotometry, potentiometry, freezing point depression, conductometry and NMR spectroscopy. In addition to the four mononuclear complexes (pq-r = 110, 120, 130 and 11-2), the formation of two binuclear, so far unknown complexes (pq-r = 23-2 and 24-2) was revealed. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
(75 reference statements)
1
20
0
Order By: Relevance
“…Giroux et al reported that given the same conditions, precipitate also appears in the case of La 3+ , Eu 3+ , Dy 3+ , Er 3+ , and Lu 3+ ions around pH = 8 or at slightly higher pH when Gluc À is in excess [7]. In their study, seven complexes were described to form with all the five studied lanthanide cations: ML [26], and a precipitate appears at pH = 8, which was proven to have the composition of NdGlucH À1 OH in our previous work [27]. However, precipitation does not occur in the Nd 3+ -ÀGluc À system at pH > 12, which raises concerns of increased solubility since the complex formation was scarcely studied at pH higher than twelve [9,28], although this hyperalkaline medium [10] and high ionic strength (I = 5.3-7.4 M) [11] is inherent to radioactive depositories.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Giroux et al reported that given the same conditions, precipitate also appears in the case of La 3+ , Eu 3+ , Dy 3+ , Er 3+ , and Lu 3+ ions around pH = 8 or at slightly higher pH when Gluc À is in excess [7]. In their study, seven complexes were described to form with all the five studied lanthanide cations: ML [26], and a precipitate appears at pH = 8, which was proven to have the composition of NdGlucH À1 OH in our previous work [27]. However, precipitation does not occur in the Nd 3+ -ÀGluc À system at pH > 12, which raises concerns of increased solubility since the complex formation was scarcely studied at pH higher than twelve [9,28], although this hyperalkaline medium [10] and high ionic strength (I = 5.3-7.4 M) [11] is inherent to radioactive depositories.…”
Section: Introductionmentioning
confidence: 80%
“…However, precipitation does not occur in the Nd 3+ -ÀGluc À system at pH > 12, which raises concerns of increased solubility since the complex formation was scarcely studied at pH higher than twelve [9,28], although this hyperalkaline medium [10] and high ionic strength (I = 5.3-7.4 M) [11] is inherent to radioactive depositories. Considering that Kutus et al proved the formation of polynuclear Nd 3+ ÀGluc À complexes as pH increases [26] and Giroux et al reported that lanthanides tend to form M 2 L 2 -H À5 À in alkaline media, the redissolving precipitate implicates that dimer or polynuclear complexes can be present in hyperalkaline medium which is also foreshadowed by the characteristic of Nd 3+ to dimerize even as hydroxide in Nd 2 (OH) 2 4+ form [29].…”
Section: Introductionmentioning
confidence: 99%
“…In theory, high organic acid concentration also leads to increased availability of the complexation agent. However, any occurring complexation mediated contribution to the overall leaching process will be diminished with decreasing pH and might not be compensated by the increased concentration of the complexing agent [5,27]. In order to compare the effect of different phosphorus sources on organic acid production, the PVK medium was modified by substitution of calcium phosphate (= 32.2 mM PO 4 3− ) with either KH 2 PO 4 or K 2 HPO 4 (= 2.7 mM PO 4 3− ).…”
Section: Optimization Of Pvk Medium To Enhance Organic Acid Productionmentioning
confidence: 99%
“…They suggested that deprotonation occurred in saccharide moieties according to the results of potentiometric measurements and 13 C NMR and Mössbauer spectroscopic methods. Rubini and co-workers , and Kutus et al prepared a series of d -gluconate complexes of several lanthanide ions. Bertani and co-workers prepared an aluminum complex of d -gluconate.…”
Section: Introductionmentioning
confidence: 99%
“…Burger and co-workers prepared a copper complex of d -gluconate . As a matter of fact, some complexes were obtained in acidic environments, and deprotonations on the OH of the d -gluconate moiety were proposed to occur in these complexes on the basis of the various experimental results such as pH potentiometry, ESI mass spectrometry, and NMR spectroscopy. Kiss and co-workers prepared some vanadium (IV, V) complexes using two aldaric acids ( d -saccharic acid, mucic acid) as ligands in acidic solutions. They suggested that deprotonation took place on the OH group of the ligand according to the experimental results of pH potentiometry and EPR, NMR, and UV–vis spectroscopy .…”
Section: Introductionmentioning
confidence: 99%